Economic burden of surgical management of surgical site infections following hip and knee replacements in Calgary, Alberta, Canada. (3rd June 2022) - Mponponsuo, Kwadwo; Leal, Jenine; Puloski, Shannon; Chew, Derek; Chavda, Swati; Au, Flora; Rennert-May, Elissa
Abstract: Objective: To evaluate the cost of 1-stage and 2-stage revisions, debridement, antibiotic and implant retention (DAIR) and DAIR with liner exchange for complex surgical site infections (SSIs) following hip and knee replacements. Design: Retrospective population-based economic analysis of patients undergoing intervention for SSIs between April 1, 2012 and March 31, 2019. Setting: The study was conducted in the Calgary zone of Alberta Health Services (AHS) in Canada. Participants: Individuals >18 years with complex SSI following hip or knee replacement. Methods: Patients with complex SSIs were identified using the AHS infection prevention and control database. A combination of microcosting and gross costing methods were used to estimate 12- and 24-month costs following the initial hospital admission for arthroplasty. Subgroup, inverse Gaussian and γ regression analyses were used to evaluate the impact of age and comorbidities on cost. Results: In total, 142 patients with complex SSIs were identified, with a mean age of 66.8 years. Total direct medical costs in United States dollars of 2-stage revisions were ($100, 992 (95% CI, 34, 587–167, 396) at 12 months. The 1-stage revision ($41, 176; 95% CI, 23, 361–58, 991), DAIR with liner exchange ($41, 267; 95% CI, 29, 923–52, 612) and DAIR ($46, 605; 95% CI, 15, 277–76, 844) were associated with fewer costs at 12 months. Age >65 years and chronic complications of diabetes and hypertension were associated with increased costs in subgroup and regression analysis. Conclusions: Medical costs are highest at 12 months and for 2-stage revisions in hip and knee complex SSI cases. Further work should explore surgical outcomes correlated with costs to enhance patient care.